2012
DOI: 10.1680/tran.10.00024
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the number of bicycle commuters

Abstract: The present study confirmed that commuter cyclists take on different mode-choice behaviours depending on whether they have experienced leisure cycling prior to becoming a commuter cyclist. In a survey conducted for the present study, about 57% of the sampled commuter cyclists had experience as a leisure cyclist. The remaining individuals were inexperienced at leisure cycling. A discrete mode-choice model, which has been widely used in mode-choice studies, was applied separately for each commuter-cyclist group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
6
1
1
Order By: Relevance
“…This finding conflicts with several previous studies in which researchers have suggested that cycling for leisure or sport may have a positive effect on cycle commuting (Kroesen & Handy, 2013;Lee, Park, & Sohn, 2012;Park, Lee, Shin, & Sohn, 2011;Stinson & Bhat, 2004;Xing, Handy, & Mokhtarian, 2010). The explanation for this result may lie in the image of cycle commuting which, in countries where cycling is uncommon, is viewed as dangerous, demanding and stressful; often in contrast to leisure cycling which is regarded as calm, peaceful and liberating (Gardner, 1998).…”
Section: Carcontrasting
confidence: 67%
“…This finding conflicts with several previous studies in which researchers have suggested that cycling for leisure or sport may have a positive effect on cycle commuting (Kroesen & Handy, 2013;Lee, Park, & Sohn, 2012;Park, Lee, Shin, & Sohn, 2011;Stinson & Bhat, 2004;Xing, Handy, & Mokhtarian, 2010). The explanation for this result may lie in the image of cycle commuting which, in countries where cycling is uncommon, is viewed as dangerous, demanding and stressful; often in contrast to leisure cycling which is regarded as calm, peaceful and liberating (Gardner, 1998).…”
Section: Carcontrasting
confidence: 67%
“…The results of this study are also in line with the findings of other scholars, who found relationships between non-work activities and commute travel by all modes, particularly by bike. In the MENA regions, non-work variables such as entertainment place, shopping/entertainment mode choice, number of non-work activities, and presence of attractive shops in the neighborhood are associated with commuting length [45][46][47].…”
Section: Contextual Differences With High-income Countriesmentioning
confidence: 99%
“…Too dangerous, lack of sufficient fitness, lack of motivation, lack of facilities at work (showers, bike racks, etc. ), no bike lanes, personal safety during journey, bad weather, lack of proper lighting, distance, topography, lack of safe parking at destination, lack of cycling knowledge or experience, too much traffic, uncomfortable, difficulties with trip chaining, need to carry things, air pollution, free car parking at work, lack of time, and bad road conditions (3,4,6,9,16,(18)(19)(20)(21)(22).…”
Section: Cycling Habits and Other Psychological Variables Affecting Cmentioning
confidence: 99%